The Effect of Work System Digitalization and Competence on Employee Performance (A Study on Employees of PT Rizqoena Sentosa Raya) - Leo Difna Hira Nirfani; Dharliana Ayu Hardjowikarto; Juwita (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effect of work system digitalization and competence on employee performance at PT Rizqoena Sentosa Raya, a building and development company in Cirebon Regency, West Java, Indonesia. Using a quantitative associative research design, data were collected from 30 respondents through simple random sampling (Slovin formula, error tolerance 5%) and analyzed using multiple linear regression via IBM SPSS. The results indicate that work system digitalization has a positive and significant partial effect on employee performance (t = 7.311, sig. < 0.001), and competence has a positive and significant partial effect on employee performance (t = 5.772, sig. < 0.001). Simultaneously, both variables exert a positive and significant influence on employee performance (F = 42.344, sig. < 0.001). The model explains 75.8% of variance in employee performance (R² = 0.758; Adjusted R² = 0.740), with work system digitalization emerging as the more dominant predictor (β = 0.692) relative to competence (β = 0.546). These findings suggest that building and development organizations can optimize employee performance by pursuing concurrent investment in digital work system integration and workforce competence development.